Evaluation of synthetic household wastewater quality using artocarpus heterophyllus peel as a natural coagulant - Priyatharishini, Mardarveran (2020)
The use of chemical coagulants in wastewater treatment developed detrimental effects on the environment. In order to overcome this, the application of natural coagulant has been widely explored by researchers as an alternative solution to chemical coagulants. Natural coagulants were considered to be safe, biodegradable and cheap. Research on utilization of Artocarpus heterophyllus (jackfruit) peel in purifying household wastewater has yet to be discussed in literature till date. Thus, this study aimed to characterize and identify the coagulant properties of Artocarpus heterophyllus peel for synthetic household wastewater purification as well as obtaining the best condition for coagulation process using response surface methodology (RSM) technique. Artocarpus heterophyllus peel extract coagulant is prepared by drying and grinding the peel into fine powder. Proximate analysis was performed on the dried Artocarpus heterophyllus peel powder. As for the preparation of coagulant, the peel powder was soaked in distilled water and stirred for an hour. The mixture was filtered and the obtained filtrate was used as coagulant in the experiment. The characterization tests of the coagulant were carried out based on analyses of surface charge, functional group and morphology. The coagulation jar test experiment was carried out and two main variables were studied which included pH of synthetic household wastewater and dosage of coagulant. After testing, the water quality of the treated wastewater was determined by measuring the concentration of chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solids (TSS) and turbidity. The RSM method based on central composite design (CCD) was used to obtain the best condition of parameters that works well in purifying household wastewater. The proximate analysis revealed the presence of protein and carbohydrate in the peel which are among the significant components suggested in assistance of the coagulation process. The surface charge of the synthetic wastewater is positive at pH 2 and later turned to be negative as the pH is increased up to pH 12. The measured zeta potential of the coagulant was -25.2 mV at its original pH, 6.95 possibly causing charge neutralization of opposite charges. This coagulant also comprised of functional groups such as carboxyl and hydroxyl groups in which all of these groups were salient for coagulation efficiency. Morphology analysis revealed that the addition of natural coagulant modified the colloid particles by providing voided pores that allowed the binding mechanism. From the RSM results, the best condition for the Artocarpus heterophyllus peel coagulant when pH of wastewater at 2.1 and coagulant dosage of 58 mg/L. The validation experiments revealed the removal of turbidity, TSS, BOD and COD were 80.7 %, 77.5 %, 34.3 % and 34.6 % respectively. The model obtained was significant with p-value < 0.05. It is suggested that this model had a maximum point which is likely to be the best condition and possible for the optimization process. The findings showed a higher reduction in TSS and turbidity by using this natural coagulant which is very important in primary treatment of wastewater. This can serve as a starting point for future studies to explore this new type of natural coagulant as well to replace the commercial chemical coagulants in water and wastewater treatment.